Crises in the financial regulation of finance-led capitalism: a Minskyan analysis - Ana Rosa Ribeiro de Mendonça; Simone Deos (Revue de la Régulation)
Financial markets are subject to more developed regulatory mechanisms than those of other sectors of the economy. This can be explained by the nature of financial transactions and by the extremely harmful consequences of financial crises for the entire economic system. The current regime of banking regulation is based on risk sensitive capital requirements and on market-based risk measurement and management, and it could be termed “supervised auto regulation”. The hypothesis put forward in this article is that this regulatory framework is not suitable for capitalist economies with highly developed financial systems and very little so for our specific finance-led accumulation regime. In the current scenario of widespread crisis, it seems especially relevant to analyze financial and, more specifically, banking regulation, from a Minskyan perspective.